The moment of the criminal bankruptcy completing and I. S. Tishkevich doctrine of the unfinished crime value for this moment determining - Zakhilko, Kiryl S. (Journal of the Belarusian State University. Law, 2019)
Determining of the moment of completing of criminal bankruptcy is connected with the definition of the boundaries of this crimes, the proper criminal-legal assessment of the deed, as well as the effectiveness and practical applicability of art. 239–241 of the Criminal Code of the Republic of Belarus. In the science of criminal law, this problem is debatable. However, it did not receive detailed consideration in the domestic literature with reference to the specifics of the Belarusian legislation. In view of significant contribution of professor I. S. Tishkevich in the development of the doctrine of an unfinished crime, it seems advisable to consider his theoretical views in refraction for this discussion. This is extra topical in eve of the sentennial of the scientist. Consideration of the declared problems allowed coming to conclusions that the real public danger of criminal bankruptcy in modern conditions inconsistent with the legislative reflection of the moment of its completing. The findings can be used to improve legislation and law practice.